A General Crosslinker Strategy to Realize Intrinsic Frozen Resistance of Hydrogels. Issue 42 (2nd September 2021) - Zhang, Dong; Liu, Yonglan; Liu, Yanghe; Peng, Yipeng; Tang, Yijing; Xiong, Liming; Gong, Xiong; Zheng, Jie
Abstract: Development and understanding of antifreezing materials are fundamentally and practically important for materials design and delivery. However, almost all of antifreezing materials are either organic/icephobic materials containing no water or hydrophilic hydrogels containing antifreezing additives. Here, a general crosslinking strategy to fabricate a family of EGINA‐crosslinked double‐network hydrogels with intrinsic, built‐in antifreezing and mechanical properties, but without any antifreezing additives is proposed and demonstrated. The resultant hydrogels, despite large structural and compositional variations of hydrophilies, electrolytes, zwitterions, and macromolecules of polymer chains, achieved strong antifreezing and mechanical properties in different environments including solution state, gel state, and hydrogel/solid interfaces. Such general antifreezing property of EGINA‐crosslinked hydrogels, regardless network compositions, is likely stemmed from their highly hydrophilic and tightly crosslinked DN structures for inducing strong water–network bindings to prevent ice crystal formation from free waters in hydrogel networks. EGINA‐crosslinked hydrogels can also serve as a key component to be fabricated into smart windows with high optical transmittance and supercapacitors with excellent electrochemical stability at subzero temperatures. This work provides a simple, blueprint antifreezing design concept and a family of antifreezing hydrogels for the better understanding of the composite–structure–property relationship of antifreezing materials and the fundamentals of confined water in wet soft materials. Abstract : A simple and universal crosslinking strategy to fabricate a family of EGINA‐crosslinked materials with intrinsic, built‐in antifreezing and mechanical properties, but without any antifreezing additives is demonstrated. The resultant EGINA‐crosslinked materials, consisting of a wide range of compositions (hydrophiles, electrolytes, zwitterions, macromolecules), enable achievement of their antifreezing properties at −20 °C in solution, gel state, and hydrogel/solid interfaces.